Development of a composite index for the assessment of food systems in the Philippines - Maria Julia Golloso-Gubat; Angelina Felix; Nancy A. Tandang; Cecilia Cristina S. Acuin; Prudenciano U. Gordoncillo (Frontiers in Nutrition)
Food system assessment is vital in providing informed decisions for relevant transformations and policy shifts. In the present study, we developed and a composite index that can be utilized to quantitatively assess the status and/or performance of the food systems in the Philippines. Initially, a set of indicators were generated by Delphi approach, and relevant local data were used to develop algorithms to quantitatively operationalize the indicators which were subsequently grouped into domains by Principal Component Analysis (PCA). Equal weights were applied to indicators, and the linear additive aggregation technique was employed. The robustness of the model was also tested by uncertainty and sensitivity tests. Finally, the utility of the index was tested to describe the status of food systems in the Philippines at the across regions. Results indicate differences in regional food system scores; Central Luzon, CALABARZON, and CAR have higher scores than the other regions, while Bicol, Western Visayas, and Davao obtained relatively low scores. The sub-national level assessment indicates differences in food system concerns and priority areas across the country, providing implications for context-specific program and policy development.